2019
DOI: 10.1016/j.marpolbul.2019.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Macro-litter in surface waters from the Rhone River: Plastic pollution and loading to the NW Mediterranean Sea

Abstract: We present here the first estimates of floating macro-litter in surface waters from the Rhone River, based on monthly visual observations during 1-year period (2016-2017). Plastic represented 77% of the identified items, confirming its predominance in riverine floating litter. Fragments (2.5-50 cm) and Single Use Plastics (i.e. bags, bottles and cover/packaging) were among the most abundant items. Frequent non-plastic floating litter were paper items such as packaging material and newspapers, and metal items (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 42 publications
(55 reference statements)
5
107
0
Order By: Relevance
“…Once entered a river (see Figures 2 and 3), plastic transport is influenced by hydrological factors such as water level, flow velocity, and discharge (van Emmerik et al, 2018). Several studies found a positive correlation between river discharge and plastic transport (Castro-Jiménez et al, 2019;Moore et al, 2011). Increased water levels can remobilize plastics that are temporarily accumulated on riverbanks or in vegetated riparian zones.…”
Section: Origin and Fate Of Riverine Plastic Debrismentioning
confidence: 99%
“…Once entered a river (see Figures 2 and 3), plastic transport is influenced by hydrological factors such as water level, flow velocity, and discharge (van Emmerik et al, 2018). Several studies found a positive correlation between river discharge and plastic transport (Castro-Jiménez et al, 2019;Moore et al, 2011). Increased water levels can remobilize plastics that are temporarily accumulated on riverbanks or in vegetated riparian zones.…”
Section: Origin and Fate Of Riverine Plastic Debrismentioning
confidence: 99%
“…The period and frequency of counting and sampling vary for each river from 3 d in total to a weekly assessment for a period of 12 months. All measurements conducted by this study were done in 2018, except the measurements in 2017 in the Tiber and the Rhône, conducted by Crosti et al [20] and Castro-Jiménez et al [28] respectively. In Europe, measurements were done in Italy, The Netherlands, and France.…”
Section: Measured Waterwaysmentioning
confidence: 99%
“…The Rhône river in France flows into the Mediterranean sea. Results from the study Castro-Jiménez et al [28] are used in this study. The plastic flux is measured in the middle of the river, with an observation width of 65 m. In Asia, measurements were done in Vietnam, Indonesia, Thailand, and Malaysia.…”
Section: Measured Waterwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…All monitoring long-term efforts of floating (plastic) litter to date have been done using the visual counting method (e.g. Crosti et al, 2018;Castro-Jiménez et al, 2019;van Emmerik et al, 2019b). Floating litter observations can also be facilitated through citizen science.…”
Section: Floating Littermentioning
confidence: 99%